2011
DOI: 10.1007/s12524-011-0065-7
|View full text |Cite
|
Sign up to set email alerts
|

Yield Estimation Model and Water Productivity of Wheat Crop (Triticum aestivum) in an Irrigation Command Using Remote Sensing and GIS

Abstract: Crop yield estimation has an important role on economy development and its accuracy and speed influence yield price and helps in deciding the excess or deficit production conditions. The water productivity evaluates the irrigation command through water use efficiency (WUE). Remote sensing (RS) and geographical information system (GIS) techniques were used for crop yield and water productivity estimation of wheat crop (Triticum aestivum) grown in Tarafeni South Main Canal (TSMC) irrigation command of West Benga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This problem could be solved by using the EVI, which was proposed to reduce atmospheric influences and decouple the canopy background signal, according to Deng et al [32] and Son et al [31]. Currently, studies have been conducted using the SAVI by taking the influence of the soil background in the early period and the interference of high vegetation coverage in the late period into consideration [33][34][35]. Guo et al [34] incorporated temporal remote sensing vegetation indices (VIs) and the wheat grow-PROSAIL model-simulated VIs to forecast regional crop yields in Yanhu Farm and Baimahu Farm.…”
Section: Introductionmentioning
confidence: 99%
“…This problem could be solved by using the EVI, which was proposed to reduce atmospheric influences and decouple the canopy background signal, according to Deng et al [32] and Son et al [31]. Currently, studies have been conducted using the SAVI by taking the influence of the soil background in the early period and the interference of high vegetation coverage in the late period into consideration [33][34][35]. Guo et al [34] incorporated temporal remote sensing vegetation indices (VIs) and the wheat grow-PROSAIL model-simulated VIs to forecast regional crop yields in Yanhu Farm and Baimahu Farm.…”
Section: Introductionmentioning
confidence: 99%
“…MODIS data have been successfully used for yield estimation and prediction (Bala and Islam, 2009;Doraiswamy et al, 2004;Huang et al, 2012;Mkhabela et al, 2011;Ren et al, 2008;Shunlin et al, 2004;Son et al, 2013c). In particular, studies have used remotely sensed vegetation indices, such as the normalized difference vegetation index (NDVI) (Kastens et al, 2005;Mkhabela et al, 2011;Mkhabela et al, 2005;Moriondo et al, 2007;Quarmby et al, 1993;Ren et al, 2008), the enhanced vegetation index (EVI) (Bolton and Friedl, 2013;Kyoungdo et al, 2013;Shunlin et al, 2004), and the soil-adjusted vegetation index (SAVI) (Gontia and Tiwari, 2011;Mandal et al, 2007;Noureldin et al, 2013;Panda et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In Skakun's study, yield estimation was made using only Landsat-8, only Sentinel-2 and NDVI value obtained from the combined model and R 2 values were found to be 0.64, 0.88, and 0.90, respectively. [27] compared the NDVI and SAVI results and they indicated that SAVI performed better than NDVI.…”
Section: Introductionmentioning
confidence: 99%